CADD-10. 2-HYDROXYOLEIC ACID, A NOVEL MEMBRANE LIPID REGULATOR, DEMONSTRATES CLINICAL ACTIVITY IN HIGH-GRADE GLIOMA. (5th November 2018) - Hanson, Derek; Escriba, Pablo; Perier, Antione; Tur, Vicenc
Abstract: 2-hydroxyoleic acid (2OHOA) is the first potential anti-cancer drug to act by modification of cell membrane lipid content. Through its unique mechanism, 2OHOA targets the membrane lipid composition and organization of cancer cells, altering downstream signaling cascades that promote tumor cell proliferation. Cancer cells demonstrate an abnormal membrane lipid microdomain phenotype rich in phosphatidylethanolamine (PE) and phosphatidylcholine (PC) and relatively sphingomyelin-poor when compared to non-malignant cells. Through its direct activity on sphingomyelin synthase 1, 2OHOA is able to alter the lipid membrane composition of cancer cells and restore the membrane to a normal sphingomyelin-rich phenotype. Ras is only able to propagate its signal cascade when located near the cell membrane and demonstrates an affinity for PE/PC microdomains. 2OHOA exposure results in replacement of PC and PE domains with sphingomyelin, thereby displacing Ras from the cell membrane to the cytoplasm where it is inert. Thus through normalization of the lipid membrane composition, 2OHOA is able to effectively downregulate the Ras signaling cascade, resulting in decreased tumor cell proliferation. A European phase I/IIa trial of 2OHOA in adult patients with high-grade glioma and other advanced solid tumors has recently been completed. The results are promising with five refractory malignant glioma patients demonstrating objective clinical benefit by RANO criteria for six or more months, including one glioblastoma patient with a sustained partial response (93% regression from baseline) of the primary lesion for over thirty-three months of therapy. The drug has been very well-tolerated in adult patients with minimal toxicity. A European phase IIb trial for adult patients with newly diagnosed high-grade glioma combining 2OHOA with standard therapy (radiotherapy and temozolomide) is being planned. A pediatric phase I trial of 2OHOA for children with high-grade glioma and other advanced solid tumors is due to open in the United States in 2018.